Obstructive sleep apnea risk and determinant factors among type 2 diabetes mellitus patients at the chronic illness clinic of the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Worku, Abebe; Ayele, Eleni; Alemu, Shitaye; Legese, Gebrehiwot Lema; Yimam, Samrawit Meles; Kassaw, Getasew; Diress, Mengistie; Asres, Mezgebu Silamsaw (Frontiers in Endocrinology, 2023)
Introduction Obstructive sleep apnea is a sleep complaint among type 2 diabetes mellitus patients that has a deleterious effect on health with immediate and long-term impacts. Despite its impacts, data on the magnitude and predictors of obstructive sleep apnea among type 2 diabetes mellitus patients in Ethiopia is still limited. Thus, this study was conducted to determine how common a high risk of obstructive sleep apnea is and its predictors among type 2 diabetes mellitus patients receiving follow-up care at the chronic illness follow-up clinic at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2022. Methods An institution-based cross-sectional study was conducted. Interviewer-administered questionnaires and physical measurements with standard instruments were used to collect the required data. The collected data were entered into EpiData 4.6 and exported into STATA 14. Both Bivariable and multivariable binary logistic regression analyses were done to identify factors associated with a high risk of obstructive sleep apnea. Variables with a p-value ≤0.05 in the multivariable logistic regression analysis were declared as significantly associated with a high risk of obstructive sleep apnea. Results A total of 319 type 2 diabetes mellitus patients with a median age of 58 years participated in our current study. The overall prevalence of a high risk of obstructive sleep apnea among the study participants was 31.97% (95%CI: 27.06, 37.32). On multivariable logistic analysis, a neck circumference of ≥40 cm (AOR=4.33, 95%CI 1.37, 13.72), physical inactivity (AOR=2.29, 95%CI 1.15, 4.53), comorbid hypertension (AOR=4.52, 95%CI 2.30, 9.18), and male sex (AOR=8.01, 95%CI 3.02, 21.24) were associated with a high risk of obstructive sleep apnea. Conclusion and recommendation The prevalence of a high risk of obstructive sleep apnea among type 2 diabetes mellitus patients remains high. A neck circumference of ≥40 cm, physical inactivity, comorbid hypertension, and male sex were significantly associated with a high risk of obstructive sleep apnea among type 2 diabetes mellitus patients. Screening and evaluation of type 2 diabetes mellitus patients for obstructive sleep apnea are recommended to avoid the negative impacts.